Characterizing the Response of TAC- and CAR-Engineered T cells Following Antigenic Stimulation - Lau, Vivian Wing Chong (My University, 2018)
T lymphocytes engineered with chimeric antigen receptors (CARs) have shown remarkable success in the treatment of leukemias. Conventional CARs seek to recapitulate TCR and costimulatory signals through fusion of T cell signaling elements into a single receptor. The robust anti-tumor activity of CAR T cells is often accompanied by debilitating toxicities due to excessive T cell activation and cytokine production following infusion. Our lab has generated a novel chimeric receptor termed T cell antigen coupler (TAC), which is designed to engage native T cell signaling domains for cellular activation. In a murine xenograft model, we previously found that TAC T cells mediated rapid tumour regression in the absence of toxicities. Comparatively, CAR T cells elicited significant lethal toxicities to the mice due to reactivity against an unspecific antigen that resulted in excessive proliferation and cytokine production in vivo. Here, we report that TAC and CAR T cells have fundamentally different biology, both at rest, and during activation. TAC T cells were more sensitive to the context of stimulation compared to CAR T cells. Whereas TAC T cells can discriminate between antigen bound to a bead, or antigen present on a cell, CAR T cells do not make the same distinction and responds equally well to both. Compared to several different CAR constructs, TAC T cells are less prone to tonic signaling and T cell differentiation in the absence of antigen. These findings support that TAC T cells may pose a safety benefit as a cancer immunotherapy, due to its distinct biology from CAR T cells that enables them to require more stringent contexts for activation.
Keywords: immunology; t cells; immunotherapy; gene therapy; cancer; genetic engineering; immuno-oncology; chimeric antigen receptors